Herbicides Applied at or Shortly after Seeding Are Effective for Weed Control in Seedling Buffalograss. Issue 1 (12th November 2015) - Li, Luqi; Sousek, Matthew D.; Reicher, Zachary
Abstract : Herbicides applied shortly after seeding of buffalograss [ Buchloe dactyloides (Nutt.) Engelm.] can help reduce weed pressure and maximize establishment of buffalograss. This study evaluated 12 relatively recently developed herbicides for turf safety and weed control when applied at seeding or 0 or 2 weeks after emergence (WAE) of 'Bowie' or 'Sundancer' buffalograss. Primary weed species on the site were common purslane ( Portulaca oleracea L.), redroot pigweed ( Amaranthus retroflexus L.), and/or yellow foxtail [ Setaria lutescens (Weigel ex Stuntz) F.T. Hubb.]. Regardless of cultivar, untreated checks had <15% buffalograss cover and >53% weed cover by 6 WAE, whereas most of the herbicide treatments resulted in >80% buffalograss cover and <20% weed cover. Mesotrione, sulfentrazone, quinclorac, carfentrazone, simazine, amicarbazone, sulfentrazone + quinclorac, carfentrazone + quinclorac, or sulfentrazone + prodiamine applied either at seeding or 0 WAE are safe on Bowie or Sundancer buffalograss, effectively minimize weed pressure, and maximize buffalograss establishment. Herbicides applied at 2 WAE were less effective than earlier applications at minimizing weed pressure and resulted in lower buffalograss establishment.